PRODUKTIVITAS DAN LAJU DEKOMPOSISI SERASAH MANGROVE DI KAWASAN KONSERVASI MANGROVE DAN BEKANTAN (KKMB) KOTA TARAKAN KALIMANTAN UTARA - Hardianto .; Karmila .; Yulma Yuki (Jurnal Harpodon Borneo, 2015)
Other than for recreation purpose, Mangrove forest in Conservation Area for Mangrove and Bekantan also serve as basis for food chain where aquatic organism live. Mangrove also has high productivity. Litter productivity from several mangrove species as follows, 1.12 g/m2/day for Sonneratia alba, 0,82 g/m2/day for Rhizophora apiculata, 0.64 g/m/day for Bruguivera parviflora, and 0.52 g/m2/day for Avicennia alba. Litter decomposition rate for several mangrove species as follows, 0.35 g/day for Sonneratia alba, 0.30 g/day for Avicennia alba, 0.20 g/day for Bruguiera parviflora and the lowest one is 0.13 g/day for Rhizophora apiculata. Key word : litter productivity, litter decomposition, KKMB, Tarakan city